1990
DOI: 10.1128/jcm.28.9.2087-2093.1990
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Mycoplasma pneumoniae pneumonia: sensitivities and specificities of serology with lipid antigen and isolation of the organism on soy peptone medium for identification of infections

Abstract: The sensitivities and specificities of isolation and serology for detection of Mycoplasma pneumoniae infections were determined for 3,546 pneumonia patients for whom both isolation and serological data were available. Soy peptone, fresh yeast extract, horse serum-supplemented agar, and diphasic medium were employed for isolation, and the lipid antigen of M. pneumoniae was used for serodiagnosis by complement fixation. The number of M. pneumoniae colonies most frequently detected was 200 to 600 per throat swab,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
5

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 33 publications
1
29
0
5
Order By: Relevance
“…For scientific purposes, M. pneumoniae culture is mostly performed with cell‐free formulations such as Hayflick's, New York City, Soy Peptone or SP‐4 medium [42,43]. The last formulation, which had initially been developed for the isolation of Spiroplasma spp., is most effective.…”
Section: Culture Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…For scientific purposes, M. pneumoniae culture is mostly performed with cell‐free formulations such as Hayflick's, New York City, Soy Peptone or SP‐4 medium [42,43]. The last formulation, which had initially been developed for the isolation of Spiroplasma spp., is most effective.…”
Section: Culture Techniquesmentioning
confidence: 99%
“…Kenny et al. found sensitivities of 53% and 64% of serology and culture, respectively, when the other approach was regarded as the reference [42]. Similarly, it has been demonstrated that only 58% of patients with positive mycoplasma culture show a four‐fold or greater increase in CF antibody titer [68].…”
Section: Nucleic Acid Amplificationmentioning
confidence: 99%
“…Serologic testing is still primarily used by clinicians in order to establish the diagnosis of Mycoplasma infection; however, negative serologic testing has been seen in PCR confirmed CNS infections [32]. Routine serologic methods used on serum for detection of antibodies against M. pneumoniae include several methods such as complement fixation, immunofluorescence and enzyme immunoassays [83][84][85][86][87][88][89]. Complement fixation is the most widely accepted method [83].…”
Section: Serologymentioning
confidence: 99%
“…En effet, plusieurs études ont retrouvé un manque de corrélation entre une PCR positive et la réponse immunitaire avec apparition d'anticorps. Bien que cette discordance apparente soit également connue pour la culture et la sérologie [157], elle demande réflexion. Plusieurs explications à cette discordance entre culture ou PCR positives et absence d'anticorps ont été avancées :…”
Section: Rôle De La Pcr Pour Le Diagnostic Des Infections à M Pneumounclassified